Pre-marital education strategies for deaf people with disabilities as family resilience in indonesia - Umi Hani’atul Afifah; Baehaqi; M. Jamal; Muhammad Syakur; Sumarjoko; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2024)
Premarital education is one of the Ministry of Religious Affairs' strategic programs to equip prospective brides and grooms with the knowledge, skills, and mental preparedness to build a family that is sakinah, mawaddah, and rahmah. However, people with deaf disabilities still face serious obstacles in accessing these services, mainly due to communication barriers and limited inclusive learning facilities. As a result, their understanding of the rights and obligations of husband and wife, reproductive health, and strategies for managing domestic conflicts tends to be less than optimal, thereby increasing the potential vulnerability of the family. This article aims to examine the urgency of inclusive premarital counselling for deaf people with disabilities as an instrument for strengthening family resilience in Indonesia. The research method used a qualitative approach with literature study and policy analysis. The results of the study show that the provision of disability-friendly premarital counselling, for example by providing sign language interpreters, visual-based modules, and empathy-based counselling, is an urgent need. (Law Number 8 of 2016 concerning Persons with Disabilities). As well as the policy on family resilience development in the RPJMN (National Development Planning Agency 2020, Regarding the National Medium-Term Development Plan). Thus, inclusive premarital guidance for deaf persons with disabilities can serve as a preventive and promotional effort in creating strong, adaptive, and sustainable Indonesian families. In addition, premarital education programs have a strategic role in strengthening family resilience, especially for couples with deaf disabilities in Indonesia. Communication barriers often cause problems in domestic life, so inclusive and accessible education methods are needed. This article examines various strategies, such as developing modules with sign language, support from counsellors who understand the needs of the deaf community, and the use of disability-friendly digital media. Through the implementation of these strategies, deaf couples can gain a better understanding of their rights, obligations, and healthy communication patterns in marriage. Ultimately, disability-friendly premarital education can strengthen the values of togetherness and equality, as well as create strong and harmonious families in society.